Reliability & life testing handbook. Volume 2 - Kececioglu, Dimitri (DEStech Publications, 2002)
This volume includes the binomial tests of comparison and up-to-date information on Accept-Reject Tests, the Sequential Probability Ratio Test, Bayesian MTBF and Reliability Demonstration Tests, as well as other very important accelerated tests such as Arrhenius, Eyring, Bazovsky, and Inverse Power Law.
Keywords: Reliability (Engineering) -- Handbooks, manuals, etc.; Failure time data analysis -- Handbooks, manuals, etc.; Accelerated life testing -- Handbooks, manuals, etc.; elektronické knihy; electronic books